2004
DOI: 10.1007/s00268-004-7415-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Analysis of Gastroesophageal Reflux Diseases in Patients after Distal Gastrectomy

Abstract: The precise mechanisms that cause gastroesophageal reflux after distal gastrectomy remain unclear. We analyzed the endoscopic findings of the cardia and the position of the remnant stomach, which are related to gastroesophageal reflux. We retrospectively examined the records of 45 patients with Billroth I (B-I) and 39 patients with Roux-en-Y (R-Y) procedure for gastric cancer. Esophagitis was evaluated by the Los Angeles (LA) classification. The endoscopic findings of hiatus hernia were classified according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…17,18 However, the most common disadvantage of the B-I anastomosis, duodenogastric reflux caused of remnant gastritis and reflux esophagitis, as the absence of the pyloric sphincter which allows reflux of duodenal contents into the remnant stomach is well reported. 19,20 In addition, rapid passage of semiliquid food into the duodenum from the stomach results in dumping syndrome. Moreover, it is necessary to note that duodenal reflux into the esophagus is strongly associated with Barrett's esophagus or esophageal cancer and remnant stomach cancer after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, the most common disadvantage of the B-I anastomosis, duodenogastric reflux caused of remnant gastritis and reflux esophagitis, as the absence of the pyloric sphincter which allows reflux of duodenal contents into the remnant stomach is well reported. 19,20 In addition, rapid passage of semiliquid food into the duodenum from the stomach results in dumping syndrome. Moreover, it is necessary to note that duodenal reflux into the esophagus is strongly associated with Barrett's esophagus or esophageal cancer and remnant stomach cancer after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Untreated reflux esophagitis has been reported to have a greater effect on quality of life than do other conditions including angina pectoris, untreated hypertension, and duodenal ulcer. 36,37 This may account for the increasing use of Roux-en-Y reconstruction after a distal gastrectomy for gastric cancer. 18 In conclusion, our study showed that R-Y reconstruction was associated with significantly less reflux esophagitis after standard PD (but not after PPPD) and was associated with a significantly greater incidence of marginal ulcer after both standard PD and PPPD.…”
Section: Discussionmentioning
confidence: 98%
“…Grade D is a circumferential mucosal break. Endoscopic findings in hiatus hernia were classified according to the K‐form criteria 9,10 . In grade 0, the mucosal junction is below the hiatus.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopic findings in hiatus hernia were classified according to the K-form criteria. 9,10 In grade 0, the mucosal junction is below the hiatus. Grade A is a definite hiatus hernia, and a sac-shaped portion covered with gastric mucosa is seen more than 3 cm above the hiatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation